Relationship between body composition and anaerobic power with inter-limb difference dependence in Czech elite ice hockey players - Krajcigr, M.; Bahenský, P.; Vobr, R.; Marko, D.; Grosicki, G. J. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Ice hockey includes symmetrical as well as asymmetrical movements. As such, possible difference in mass and strength, as well as performance variables, may be observed between limbs. METHODS: We examined the relation between body composition and lower extremity anaerobic power in Czech elite ice hockey players with the inter-limb difference dependence. In total, 168 ice hockey players (age = 20.81, Q1 = 18.24, Q3 = 28.75) underwent body composition measurement and Wingate Anaerobic Test (WAnT). The dominant (D) and non-dominant (ND) leg was established. A Wilcoxon Signed Rank was used. The difference between the dominant and non-dominant lower extremities was evaluated using the dimensionless analysis and by setting the value for the dominant leg at 100%. RESULTS: The difference in muscle mass (MM), fat mass (FM), and WAnT outcome variables (MP, RAP, MP5sP) between the right and left leg was greater than the difference between D and ND leg. Less total body fat mass (TBFM) and more total body muscle mass (TBMM) and lower extremities muscle mass (LEMM) were associated with higher WAnT outcome values. The dimensionless analysis showed a statistically significant correlation between almost all variables. CONCLUSIONS: More TBMF and LEMM and less TBFM was better for WAnT. The difference between the right and left leg was greater than the difference between D and ND leg. If there is a difference between MM and FM of lower limbs than there could be difference between the power of lower limbs as well.